Canon 5D Mark III : from snapshots to great shots - Perello, Ibarionex (Peachpit Press, 2013)
Owners of the highly anticipated Canon 5D Mark III EOS digital SLR camera will want to view this video again and again as they master the powerful pro-level multimedia features of this new camera. Canon 5D Mark III : from snapshots to great shots ... lets viewers peer over the shoulder of expert photographer Ibarionex Perello as he shows how to use the 5D to take great still photographs and HD video, and gives them the perfect blend of photography instruction and camera reference that will take their images to the next level! Viewers will learn to take advantage of the supercharged EOS performance and stunning full frame, high-resolution image capture of the EOS 5D Mark III, as well as the special optical technologies like the 61-Point High Density Reticular AF and an extended ISO range of 100-25600. The video shows the ins and outs of the camera's advanced professional-level high definition video capabilities and how to achieve exceptional clarity and sharpness with the newly designed 22.3 megapixel full-frame CMOS sensor, DIGIC 5+ Image Processor, and shooting performance up to 6.0 fps. They'll also learn about the 5D's Intelligent Viewfinder, advanced iFCL metering system, High Dynamic Range (HDR), and Multiple Exposure mode. Along the way, viewers will pick up key skills they need to know about shooting with the 5D from an expert, and they'll master the photographic basics of composition, focus, depth of field, and much more--